1931
DOI: 10.1017/s002185960000993x
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the Sulphur of Pasture Grass. I. The Cystine Content of Pasture Grass

Abstract: 1. Organic sulphur determinations have been carried out on pasture grass at different stages of maturity. A decrease of about 39 per cent. was found in this constituent when the grass was cut for hay compared with the weekly and fortnightly stages of growth.2. The application of heavy dressings of inorganic sulphates to a good heavy clay permanent pasture produced an average increase of 8 per cent. in the organic sulphur content.3. No correlation was found between the organic sulphur and protein content of pas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1933
1933
1960
1960

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…In investigations of the sulphur content of pasture herbage, Evans (14) found that the percentage of total sulphur (dry matter basis) averaged 0-72 per cent, (weekly cuts), 0-71 per cent, (fortnightly cuts) and 0-63 per cent, (monthly cuts), the figures for organic sulphur being 0-36, 0-36 and 0-32 per cent, respectively. It will be noted that the percentages of organic sulphur in the grass cuts were very similar to the mean value for the lucerne samples, but that the latter contained only about half the amount of sulphate sulphur found in the grass samples.…”
Section: Comments Onmentioning
confidence: 99%
See 2 more Smart Citations
“…In investigations of the sulphur content of pasture herbage, Evans (14) found that the percentage of total sulphur (dry matter basis) averaged 0-72 per cent, (weekly cuts), 0-71 per cent, (fortnightly cuts) and 0-63 per cent, (monthly cuts), the figures for organic sulphur being 0-36, 0-36 and 0-32 per cent, respectively. It will be noted that the percentages of organic sulphur in the grass cuts were very similar to the mean value for the lucerne samples, but that the latter contained only about half the amount of sulphate sulphur found in the grass samples.…”
Section: Comments Onmentioning
confidence: 99%
“…Evans (14) has shown that the cystine content of pasture herbage is low, averaging about 0-1 per cent, of the dry matter. Nevertheless, it is considered that this is sufficient to account, under English conditions, for wool growth in sheep subsisting wholly on pasturage (15).…”
Section: Comments Onmentioning
confidence: 99%
See 1 more Smart Citation
“…The amount of phosphoric acid, on the other hand, was but moderate (0-73 per cent.). The significance of these data will be better appreciated by comparing them with similar data for pasture grass (12,13), lucerne (14) and swedes(2). Table VII indicate absence of information.…”
Section: Marrow Stem Kale and Thousand Head Kalementioning
confidence: 99%
“…During February, apart from a few slight night frosts, the weather was again mild and wet. Night frosts were encountered on the following dates during the period of the experiment: October 30, 31; November 1,2,8,13,14,20;December 17,22;January 7,8,9,10,11,12,13,16,27,28,29,30;February 6,7,8,9,10,23,24,26,27. It may be noted that the kale crops stood the winter remarkably well, and the plants remaining after the completion of the trials at the end of February were still green and healthy.…”
Section: Introductionmentioning
confidence: 99%